The Impact of Robotics on Employment and Motivation of Employees in the Service Sector, with Special Reference to Health Care - Mohammed Owais Qureshi; Rumaiya Sajjad Syed (Elsevier, 2014)
Background: The economy is being lifted by the new concept of robotics, but we cannot be sure of all the possible benefits. At this early stage, it therefore becomes important to find out the possible benefits/limitations associated with robotics, so that the positives can be capitalized, established, and developed further for the employment and motivation of employees in the health care sector, for overall economic development. The negatives should also be further studied and mitigated. Methods: This study is an exploratory research, based on secondary data, such as books on topics related to robotics, websites, public websites of concerned departments for data and statistics, journals, newspapers and magazines, websites of health care providers, and different printed materials (brochures, etc). Results: The impact of robotics has both positive and negative impacts on the employment and motivation of employees in the retail sector. So far, there has been no substantial research done into robotics, especially in the health care sector. Conclusion: Replacing employees with robots is an inevitable choice for organizations in the service sector, more so in the health care sector because of the challenging and sometimes unhealthy working environments, but, at the same time, the researchers propose that it should be done in a manner that helps in improving the employment and motivation of employees in this sector.